Airborne radar profiles of the Whillans, Bindschadler, and Kamb Ice Streams - Hale, Richard; Paden, John (IEDA: US Antarctic Program Data Center, 2016)
The Center for Remote Sensing of Ice Sheets (CReSIS) participated in an airborne radar survey using a BT-67 Basler aircraft over the Siple Coast of Antarctica. Five personnel deployed from November 29, 2013 to January 18, 2014 with USAP project# I-189-M. The major objective was to collect fine-resolution radar data with an ultra-wideband MCoRDS4 UHF/VHF radar depth sounder in conjunction with data from two microwave (Ku-band and Snow) radars and a Google Camera. This dataset includes reflection profiles for the three radars and ice surface and ice bottom picks for the radar depth sounder.